Transformasi Keuangan UMKM melalui Pendampingan Penyusunan Laporan Keuangan - Nurjanah, Rina; Nisawati, Inna; Saputera, Denny; Daniyah, Alifa Putri; Delima, Trianita (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
MSMEs play an important role in the Indonesian economy, but many face challenges, especially in financial management and digital marketing. This research aims to provide concrete solutions to the problems faced by Amelia Bakery, which include the lack of a structured financial recording system and optimal utilisation of digital platforms. The methods used in this community service programme include socialisation, training, technology implementation, mentoring, and periodic evaluation. The results of this activity show an increase in the ability of owners and employees to prepare financial reports manually. However, further guidance is still needed when using financial applications. With the implementation of this comprehensive solution, it is expected that Amelia Bakery can improve business performance, strengthen its position in the market, and achieve better sustainability. In addition, this activity is expected to positively impact the surrounding community and encourage the growth of other MSMEs in the region.